ANALISIS KINERJA DAN PERENCANAAN RUANG HENTI KHUSUS (RHK) SEPEDA MOTOR PADA SIMPANG BERSINYAL DI KOTA DENPASAR(STUDI KASUS: SIMPANG NOJA–SARASWATI) - I Made Kariyana; Gede Sumarda; I Gusti Ayu Made Ratih Nuratni (Fakultas Teknik, Universitas Wiraraja, 2021)
Denpasar is the capital city of Bali Province, which is the center of all activities with a total vehicle ownership of 33% of the total vehicles in Bali Province, of which 82% of vehicles are motorcycles. ) for motorcycles at the intersection. When the Covid-19 pandemic hit Indonesia, especially Denpasar City, it certainly had an impact on reducing traffic density, resulting in changes in road network performance. The purpose of this study is to determine the performance and design of RHK in accordance with the provisions of PUPR 2015 at signalized intersections in the hope that the performance of the intersection will be more effective. In determining the performance of signalized intersections, the provisions according to the Indonesian Road Capacity Manual (MKJI 1997) are used, while the Desktop & Mobile Web Application is used to determine the RHK design (Ministry of Public Works, 2013). The results of the performance analysis signaled at the Noja–Saraswati intersection during the Covid-19 pandemic had the same degree of saturation (DS) in the North, East, South, West approaches, which was 0.740. For the value of the queue length of each approach, namely the North approach 60m, East 89m, South 50m, West 55m. For the North approach delay value is 20.8 sec/pcu, East 5.3 sec/pcu, South 34.5 sec/pcu, West 13.5 sec/pcu. The RHK type P design for the East approach and the Box for the West approach with a width of 2x3.5m and a main length of 8m, the P type approach has a lane dimension of 3.5m. For the North and South approaches, RHK cannot be designed because the width of the approach does not meet the minimum requirement of 3.5m.